Nonlinear effects of remittances paid on macroeconomics in Malaysia - Taasim, Shairil Izwan (Korea Distribution Science Association, 2021)
The remittances play a major and a very critical role in promoting economic growth and development activities in the developing countries. In this study, the relationship between per capita gross domestic product (GDP) and remittances paid has been investigated based on the case studies in Malaysia from 1987 to 2018. Data was collected from various sources namely statistical yearbook by World Bank and Asian Development Bank. All variables are expressed in natural logarithm form. The technique utilized is the nonlinear autoregressive distributed lags (hereafter NARDL) approach which was introduced by Shin et al.(2014) to examine both short run and long run relationships, as well as the direction of causality, due to the asymmetric relationship between GDP and remittances. The bound test verifies asymmetric cointegration among the variables. The empirical results show that the remittances paid has a momentous short-run and long-run effect towards capital accumulation in Malaysia. Remittances also increase a positive relationship with capital accumulation for Malaysia. We found that remittances form a significant source of external capital and investment for developing countries especially Malaysia which helps in promoting economic development. Furthermore, as a developing country, foreign workers are a source of income to the receiving countries and an indicator to boost sender countries.